Le nationalisme galicien, de la transition démocratique à l’autonomie - Xosé M. Núñez Seixas (Cahiers de Civilisation Espagnole Contemporaine)
Galicia uses to be characterised as a case of an ethnically distinct area where the absence of industrial modernization, emigration and rural clientelism contributed to blocking any chance of social success for ethnonationalism. However, it is suggested here that deep changes which have affected Galician society since the 1960s and 1970s, together with the strong mobilisation campaigns promoted by newly-born left-wing nationalist groups during the 1970s and first 1980s, alongside the peculiar mixture of ideological radicalism and ever increasing pragmatism shown by the nationalist leadership, has made it possible for Galician radical left-wing nationalists to settle the basis for their later growth. The internal dynamics of the nationalist movement and its strategic adaptation to changing circumstances have contributed to breaking its isolation, although levels of national consciousness and the articulation of civil society still remain behind other European stateless nations, such as Scotland or Catalonia.